Decision Support System Using AHP and Topsis Methods in Determining Wedding Packages - Achmad Syauqi; Winny Purbaratri (bit-Tech, 2021)
Choosing a wedding package is always a problem for the prospective bride and groom. The decision support system helps the wedding organizer to make it easier for consumers to choose a wedding package. In this case, the researcher uses the AHP method to find the weight of the criteria and the TOPSIS method to rank alternative consumer choices. The criteria used in this study were 7 (seven), Makeup, Clothing, Catering, Documentation, Decoration, Number of Guests and Price. The results obtained from this study are that the system is able to produce a ranking order of wedding package options in a fast time and get the right choice